Function and analysis of capital market rates - Van Horne, James C. (Englewood Cliffs, N.J. : Prentice-Hall, 1970)
This book is designed primarily for use as a supplemement for courses in money and banking, money and capital markets and monetary policy.It deals with role of interest rates in channeling savings in an economy to investment and explains the differences in observed yields for various financial instruments.
Index
Includes bibliographies.
ucj 14/01/2019
Loans
Keywords: Interest; Capital; Finance